2020
DOI: 10.1017/s204017442000094x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal resistance to diet-induced obesity partially protects newborn and post-weaning male mice offspring from metabolic disturbances

Abstract: The rising rate of childhood overweight follows the increase in maternal obesity, since perinatal events impact offspring in a diversity of metabolic disorders. Despite many studies that have linked dietary consumption, overnutrition, or maternal obesity as the mediators of fetal metabolic programming, there are gaps regarding the knowledge about the contribution of different maternal phenotypes to the development of metabolic disturbances in offspring. This study aimed to investigate whether maternal high-fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(69 reference statements)
0
5
0
1
Order By: Relevance
“…Blood samples were obtained from the cut tip of tails and were used to determine glucose levels at 0, 5, 10, 15, 20 min. [ 26 ] In order to calculate insulin response, we analyzed the area under the curve (AUC).…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were obtained from the cut tip of tails and were used to determine glucose levels at 0, 5, 10, 15, 20 min. [ 26 ] In order to calculate insulin response, we analyzed the area under the curve (AUC).…”
Section: Methodsmentioning
confidence: 99%
“…At mating, female mice fed a HF diet were obese, as evident by increased body weight and adiposity, higher energy intake, and elevated glycemia levels. It is widely established that the offspring of HF dams exhibit rapid body weight gain and increased adiposity, partly due to increased energy intake [6,14,23,43,44], suggesting a potential impairment in the development of neuronal circuits responsible for regulating energy homeostasis. Although the mechanisms have not been fully elucidated, the significance of long-chain polyunsaturated fatty acids (LC-PUFAs) in neuronal development has been the subject of investigation [45].…”
Section: Discussionmentioning
confidence: 99%
“…A Brazilian cohort study conducted in 2015 revealed that 47% of women were classified as overweight or obese before pregnancy [4]. In addition, obesity in children and adolescents (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years old) has increased significantly. In 1975, the global prevalence of obesity was 0.7% among girls and 0.9% among boys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Simino et al proposed that let-7a was upregulated in livers at the delivery day and decreased the levels of AMP-activated protein kinase α2 (AMPKα2) protein and Lin28a, causing the metabolic disturbances of offspring from obesity-prone HFD-fed dams (OP-O) ( 26 ). They previously reported that OP-O mice presented higher hepatic TG, serum glucose/insulin and cholesterol levels, diminished Prkaa2 (the gene that encodes AMPKα2) and upregulated Fasn and Srebf1 (sterol regulatory element binding transcription factor 1) after weaning ( 134 ). This indicated that OP-O mice were early prone to developing metabolic disturbances, such as NAFLD.…”
Section: Role Of Mirnas In Both Glucose and Lipid Metabolism In Offsp...mentioning
confidence: 99%